2022
DOI: 10.1371/journal.pone.0277773
|View full text |Cite
|
Sign up to set email alerts
|

Nurse home visiting to improve child and maternal outcomes: 5-year follow-up of an Australian randomised controlled trial

Abstract: Objectives Nurse home visiting (NHV) is widely implemented to address inequities in child and maternal health. However, few studies have examined longer-term effectiveness or delivery within universal healthcare systems. We evaluated the benefits of an Australian NHV program (“right@home”) in promoting children’s language and learning, general and mental health, maternal mental health and wellbeing, parenting and family relationships, at child ages 4 and 5 years. Setting and participants Randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
1
19
0
5
Order By: Relevance
“…As per the trial’s programme logic, the early benefits to parent care, responsivity and the home learning environment that were evident at 2 years12 appear to be translating into gains for child outcomes at 6 years. Although benefits to maternal mental health that were previously evident at 3–5 years10 11 were not apparent at 6 years, benefits for measures of parenting, maternal well-being and family relationships were sustained from the preschool years.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As per the trial’s programme logic, the early benefits to parent care, responsivity and the home learning environment that were evident at 2 years12 appear to be translating into gains for child outcomes at 6 years. Although benefits to maternal mental health that were previously evident at 3–5 years10 11 were not apparent at 6 years, benefits for measures of parenting, maternal well-being and family relationships were sustained from the preschool years.…”
Section: Discussionmentioning
confidence: 88%
“…Recognising the importance of tailoring programmes to maximise impact,9 the structure incorporated evidence-based interventions (‘focus modules’), which are customisable to local subpopulations. Follow-up from 2 to 5 years demonstrated wide-ranging benefits across domains including parenting, the home environment and maternal mental health 10–12…”
Section: Introductionmentioning
confidence: 99%
“…Extending access to programs such as sustained nurse home visiting, that support families with health, education, and early parenting beginning in pregnancy may be one way to combat some of these issues. Evidence for nurse home visiting programs is substantial [ 63 , 64 ]. Studies of such programs show families who participate report considerable parenting, social, and health benefits as much as five years later, indicating the programs can provide valuable lifelong improvement to the well-being of families.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the prenatal period in shaping men tal, physical and cognitive trajectories, providing goodquality and accessible parental and familial support early in life is essential to affect this process 367 . Earlier, we presented evidence of posi tive outcomes following earlylife home visitation programs for pregnant and postpartum mothers, with benefits extending into childhood and adolescence, and huge cost savings 371,373 . These in terventions are particularly effective in selective groups.…”
Section: Invest In Interventions That Target Critical Windows Of the ...mentioning
confidence: 99%
“…This intervention continued to exhibit marked divi dends into adolescence, through reduced welfare and justice sys tem involvement 372 . A similar intervention study in Australia, that also included monthly nurse home visits for the first two years of the child's life, showed that children of mothers who received nurse visits had overall lower scores on the Strengths and Difficul ties Questionnaire, indicating fewer emotional and behavioural problems 373 . Interestingly, the same study showed positive out comes for parents across a wide range of domains, including less hostility, less parentchild conflict, higher wellbeing and qual ity of life, and increased selfefficacy.…”
Section: Early-life Home Visit Programsmentioning
confidence: 99%